2022
DOI: 10.1039/d1sc06755a
|View full text |Cite
|
Sign up to set email alerts
|

Exciton interactions in helical crystals of a hydrogen-bonded eumelanin monomer

Abstract: Eumelanin, a naturally occurring group of heterogeneous polymer/aggregate providing photoprotection of living organisms consists of 5,6-dihydroxyindole (DHI) and 5,6-dihydroxyindole-2-carboxylic acid (DHICA) building blocks. Despite their prevalence in the animal world,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…(C) Different orientations of DHI (D1-4) and the directing hydrogen bonds observed in the single crystal. 36 Copyright 2022, Royal society of chemistry. (D).…”
Section: Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(C) Different orientations of DHI (D1-4) and the directing hydrogen bonds observed in the single crystal. 36 Copyright 2022, Royal society of chemistry. (D).…”
Section: Structure Analysismentioning
confidence: 99%
“…DHI diffraction mass single crystals obtained in chloroform solution show zig-zag helical stacking. 36 The first computational study of structural characteristics of DHI-eumelanin polymers in aqueous solution was reported by Soltani et al , and it was shown that eumelanin aggregated by forming nanoscale stacks due to the reduction of hydrogen bonds between eumelanin and water, and the results showed non-covalent stacks with interlayer distances less than 3.5 Å. 11…”
Section: Structure Analysis and Physicochemical Properties Of Melaninmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Thus, over the past several decades, chemists have been motivated to develop strategies to form helical conformations, one of which involves the formation of a supramolecular helix by the self-assembly of monomers, which requires an in-depth understanding of noncovalent interactions. [10][11][12] Among these interactions, while hydrogen bonding and pÁ Á Áp stacking interactions remain to be a major interaction, 13 it has been increasingly recognized that other noncovalent interactions such as halogen, chalcogen, pnictogen and tetrel bonding can also be exploited to obtain desired aggregate structures.…”
Section: Introductionmentioning
confidence: 99%
“…Helical structures are widely found in metal–organic helicates and aromatic amide foldamers, which however have been rarely reported in pure organic compounds. Organic species undergo two ways including symmetry breaking , or chirality transfer from chiral segments to form helical structures during crystallization, whereby the chiral crystals adopt one of the chiral space groups with different chiral axes. Achiral compounds by symmetry breaking generate independent chiral crystals with equally distributed handedness. Inherent chiral species produce chiral crystals, while the helical packing is normally hard to designate due to the lack of an apparent screw sense. Consequently, chiral structure-chiroptical property relationship is still ambiguous.…”
Section: Introductionmentioning
confidence: 99%